On the interrelation of action accountability and job autonomy: Evidence from the nursing industry - Arnold, Markus C.; Posch, Arthur (Accounting, Organizations and Society, 2025)
While prior work in management accounting has mainly focused on results controls, this study investigates how action accountability as an action control and job autonomy are jointly used by supervisors in a setting in which results controls at the individual employee level are of little relevance. We analyze our research question by collecting survey data among nurses from Swiss public hospitals. We predict and find that when task complexity is high, job autonomy and action accountability are used as substitutes by the supervisor. When task complexity is low, job autonomy and action accountability have a less substitutive relation than when task complexity is high. In supplemental analyses, we also find that action accountability and job autonomy act as substitutes with respect to employee loyalty and effort when task complexity is high and less so when it is low, consistent with supervisors’ control choices. We also collect additional archival and experimental data to provide supplemental evidence for our underlying theory. Our study enhances the understanding of the use and effects of action controls in settings in which results controls at the individual employee level are of little relevance.